2023
DOI: 10.7554/elife.81084
|View full text |Cite
|
Sign up to set email alerts
|

Sensory conflict disrupts circadian rhythms in the sea anemone Nematostella vectensis

Abstract: Circadian clocks infer time of day by integrating information from cyclic environmental factors called zeitgebers, including light and temperature. Single zeitgebers entrain circadian rhythms, but few studies have addressed how multiple, simultaneous zeitgeber cycles interact to affect clock behavior. Misalignment between zeitgebers ('sensory conflict') can disrupt circadian rhythms, or alternatively clocks may privilege information from one zeitgeber over another. Here, we show that temperature cycles modulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
2
3
0
Order By: Relevance
“…We found that daytime feeding (DF) abolished DVM-like behavior. This is similar to other studies of "sensory conflict," whereby mismatches between two zeitgebers disrupt or weaken normal behavioral rhythms (Berger & Tarrant, 2023;Harper et al, 2016). DF copepods also displayed altered free-running rhythms, with notably longer periods than NF animals (28 h -30 h).…”
Section: Implications For Our Understanding Of Dvm In Natural Populat...supporting
confidence: 88%
“…We found that daytime feeding (DF) abolished DVM-like behavior. This is similar to other studies of "sensory conflict," whereby mismatches between two zeitgebers disrupt or weaken normal behavioral rhythms (Berger & Tarrant, 2023;Harper et al, 2016). DF copepods also displayed altered free-running rhythms, with notably longer periods than NF animals (28 h -30 h).…”
Section: Implications For Our Understanding Of Dvm In Natural Populat...supporting
confidence: 88%
“…We found that daytime feeding (DF) resulted in a loss of DVM-like behavior. This is similar to other studies of "sensory conflict," whereby mismatches between two zeitgebers disrupt or weaken normal behavioral rhythms (Berger & Tarrant, 2023;Harper et al, 2016). DF copepods also displayed altered free-running rhythms, with notably longer periods than NF animals (28-30 h).…”
Section: Implications For Our Understanding Of Dvm In Natural Populat...supporting
confidence: 88%
“…Investigating the factors that shape phenotypic and rhythmic diversity in an integrative way will help to understand how animals adapt to specific habitats and how these factors can contribute to overall population fitness. Differences between individuals and between levels of organization are common features of biological rhythm in various clades and habitats [59,[70][71][72], and individual differences in behavioral patterns directly feed back to the experienced ("realized") environmental cycles used for entrainment [73][74][75]. It is thus important to treat biological variation not as "background noise," but as an additional aspect of biodiversity that needs to be considered in both the mechanistic and the ecological context [28,76].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a study under sensory temporal conflict conditions in the sea anemone Nematostella vectensis showed that a misalignment of environmental light and temperature cycles resulted in disruption of the circadian behavior [ 59 ]. However, despite the arrhythmic behaviors under sensory conflict conditions, the number of 24-h cycling transcripts was similar to the control conditions, with less than half overlapping.…”
Section: Discussionmentioning
confidence: 99%